Polymeric Micells: A Review - Dipali Bawankar; Dr Sandeep Atram; Vrushabh Mandve; Aakash Bhonde; Ashutosh Puri (Asian Journal of Pharmaceutical Research and Development, 2025)
Polymeric micelles have emerged as a highly effective strategy for drug delivery and targeted therapy. These nanoscopic colloidal structures are formed through the self-assembly of amphiphilic block copolymers in aqueous environments. Compared to conventional surfactant-based micelles, polymeric micelles offer enhanced stability and are capable of encapsulating significant quantities of hydrophobic drug molecules within their core.This review explores the fundamental aspects of polymeric micelles, including their general characteristics, physical properties, morphology, size, structural organization, and the underlying chemistry. The mechanism of micelle formation is also discussed, along with various types of polymeric micelles. Special attention is given to recent advancements in their biomedical applications, particularly in the treatment of cancer and COVID-19, as well as their use in oral and transdermal drug delivery, gene therapy, and targeted delivery to the brain.